EXTRINSIC AND INTRINSIC MOTIVATION: BIBLIOMETRIC ANALYSIS-DERIVED INSIGHTS - Khairul Hafezad Abdullah; Davi Sofyan; Muhammad Zickryl Hakim Roslan; Mohd Firdaus Roslan (Jurnal Penyelidikan Sains Sosial, 2022)
Numerous studies, such as sports, education, and business, conduct extensive research on motivation. Due to the importance of precise measurements for understanding extrinsic and intrinsic motivation, an evaluation of measuring instruments is essential. The objective of this study was to assess the publishing patterns of extrinsic and intrinsic motivation in the Scopus and Web of Science databases using ScientoPy and VOSviewer. This study indicated an upsurge in extrinsic and intrinsic motivation publications, with Web of Science publications outperforming Scopus after 2000. “Psychology” has been the subject of most interest in this research domain. The current study also found that “Frontiers in Psychology” and “Computers in Human Behaviour” have become the distinct foci of extrinsic and intrinsic research. This study found that content analysis based on the examination of authors’ keywords focuses principally on “Extrinsic motivation”, “Intrinsic motivation”, and “Self-determination Theory”. Notably, this review found that “Gamification”, “Physical activity”, and “Self-efficacy” emerged as hot keywords after 2017. This bibliometric research suggests that the publication of research on extrinsic and intrinsic motivation is substantial. In addition, it provides an overview of this research domain, which may be helpful to academics and those interested in gaining a deeper understanding of this topic. Also, researchers can monitor and review studies on extrinsic and intrinsic motivation for future reference as a road map for their work.